Age and spatial distribution of the world's oldest trees. Issue 4 (2nd May 2022) - Liu, Jiajia; Xia, Shangwen; Zeng, Di; Liu, Cong; Li, Yingjun; Yang, Wenjing; Yang, Bao; Zhang, Jian; Slik, Ferry; Lindenmayer, David B.
Abstract: Extremely old trees have important roles in providing insights about historical climatic events and supporting cultural values, yet there has been limited work on their global distribution and conservation. We extracted information on 197, 855 tree cores from 4854 sites and combined it with other tree age (e.g., the OLDLIST) data from a further 156 sites to determine the age of the world's oldest trees and quantify the factors influencing their global distribution. We found that extremely old trees >1000 years were rare. Among 30 individual trees that exceeded 2000 years old, 27 occurred in high mountains. We modeled maximum tree age with climatic, soil topographic, and anthropogenic variables, and our regression models demonstrated that elevation, human population density, soil carbon content, and mean annual temperature were key determinants of the distribution of the world's oldest trees. Specifically, our model predicted that many of the oldest trees will occur in high‐elevation, cold, and arid mountains with limited human disturbance. This pattern was markedly different from that of the tallest trees, which were more likely to occur in relatively more mesic and productive locations. Global warming and expansion of human activities may induce rapid population declines of extremely old trees. New strategies, including targeted establishment of conservation reserves in remote regions, especially those in western parts of China and the United States, are required to protect these trees. Abstract : Edad y Distribución Espacial de los Árboles Más Viejos del Mundo Resumen: A pesar de que los árboles extremadamente viejos son importantes para proporcionar información sobre eventos climáticos históricos y sustentar los valores culturales, se han realizado pocos estudios sobre su distribución y conservación mundial. Extrajimos información de 197, 855 núcleos de árboles en 4, 854 sitios y la combinamos con datos (p. ej.: la OLDLIST) de otros 156 sitios para determinar la edad de los árboles más viejos del mundo y cuantificar los factores que influyen sobre su distribución mundial. Descubrimos que los árboles extremadamente viejos, mayores a mil años, son raros. De entre 30 árboles individuales que excedían los dos mil años, 27 se encontraban en la alta montaña. Modelamos la edad máxima de los árboles con variables climáticas, topográficas del suelo y antropogénicas y nuestros modelos de regresión demostraron que la elevación, la densidad poblacional humana, el contenido de carbono en el suelo y la temperatura media anual son determinantes clave de la distribución de los árboles más longevos. Específicamente, nuestro modelo pronosticó que muchos de estos árboles se encontrarán en montañas áridas y frías de alta elevación con una alteración humana limitada. Este patrón fue significativamente diferente de aquél para los árboles más altos, que tienen la probabilidad de ocurrir en localidades relativamente más productivas y de mesohábitats. El cambio climático y la expansión de la actividad humana puede inducir una rápida declinación poblacional de los árboles extremadamente viejos. Se requieren estrategias novedosas para proteger a estos árboles, incluyendo el establecimiento enfocado de reservas de conservación en regiones remotas, especialmente aquellas en la parte occidental de China y de los Estados Unidos. 全球最老古树的年龄和空间分布摘要: 古树在记录历史气候事件和支撑文化服务等方面有着重要地位。然而, 有关古树的全球分布及其保护的工作却较为缺乏。基于此, 本研究通过收集国际树轮数据库4854个地点197855棵古树的年龄数据, 并结合另外156个有最老古树分布地点的数据 (如OLDLIST), 来探索全球最老古树的年龄和影响其分布的关键因子。基于这些数据, 我们发现超过1000年的古树其实很少, 超过2000年的古树有30棵, 其中有27棵分布在高海拔山区。通过结合气候、土壤、地形和人类活动因素构建最老古树分布模型, 我们发现海拔、人口密度、土壤碳含量和年均温等是决定最老古树分布的关键因子。具体而言, 最老古树大多分布在高海拔、干冷、受人类活动干扰较少的山区。这一结论与最高的树的分布规律显著不同:它们主要分布在更湿润和高产的区域。因此, 考虑到全球变暖和人类活动扩张会诱发古树种群快速下降, 针对古树保护的专门措施就显得极为重要, 我们建议在中国和美国的西部偏远地区为当地古树设立保护区。